Cytotoxicity of the Sesquiterpene Lactones Neoambrosin and Damsin from Ambrosia maritima Against Multidrug-Resistant Cancer Cells - Saeed, Mohamed; Jacob, Stefan; Sandjo, Louis P.; Sugimoto, Yoshikazu; Khalid, Hassan E.; Opatz, Till; Thines, Eckhard; Efferth, Thomas (Frontiers in Pharmacology, 2015)
Multidrug resistance (MDR) is a prevailing phenomenon leading to chemotherapy treatment failure in cancer patients. In the current study two known cytotoxic pseudoguaianolide sesquiterpene lactones; neombrosin (1) and damsin (2) that circumvent MDR were identified. The two cytotoxic compounds were isolated using column chromatography, characterized using 1D and 2D NMR, MS and compared with literature values. The isolated compounds were investigated for their cytotoxic potential using resazurin assays and thereafter confirmed with immunoblotting and in silico studies. MDR cells overexpressing ABC transporters (P-glycoprotein, BCRP, ABCB5) did not confer cross-resistance towards neoambrosin (1) and damsin (2), indicating that these compounds are not appropriate substrates for any of the three ABC transporters analyzed. Resistance mechanisms investigated also included; the loss of the functions of the tumor suppressor TP53 and the mutated epidermal growth factor receptor (EGFR). The HCT116 p53−/− cells were sensitive to 1 but resistant to 2. It was interesting to note that resistant cells transfected with oncogenic ΔEGFR exhibited hypersensitivity (collateral sensitivity) towards neoambrosin (1) and damsin (2) (degrees of resistances were 0.18 and 0.15 for (1) and (2), respectively). Immunoblotting and in silico analyses revealed that 1 and 2 silenced c-Src kinase activity. It was hypothesized that inhibition of c-Src kinase activity may explain collateral sensitivity in EGFR-transfected cells. In conclusion, the significant cytotoxicity of 1 and 2 against different drug-resistant tumor cell lines indicate that they may be promising candidates to treat refractory tumors.